2014
DOI: 10.1590/1678-7153.201427403
|View full text |Cite
|
Sign up to set email alerts
|

Validación Española del "Learning climate questionaire" adaptado a la Educación Física

Abstract: ResumenEl objetivo de esta investigación fue analizar las propiedades psicométricas del Learning Climate Questionnaire (LCQ) adaptado a la Educación Física (EF) en una muestra española. Se pretende determinar si es un instrumento válido y fi able para su utilización en futuras investigaciones. Se administró a un total de 758 estudiantes de secundaria de 12 a 18 años, analizándose la estructura del instrumento mediante procedimientos confi rmatorios. Los análisis apoyan el modelo teórico hipotetizado de un fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
4
0
5
Order By: Relevance
“…Haerens et al, 2013;Hagger et al, 2007;Tilga et al, 2017;Williams & Deci, 1996) and Spanish (e.g. Burgueño et al, 2020;Granero-Gallegos et al, 2014;Moreno-Murcia et al, 2008) settings. Only two studies used tools that also measured competence and relatedness supportive behaviors from PE teachers (see Sa´nchez-Oliva et al, 2013;Van den Berghe et al, 2015), even though these tools have been rarely used.…”
Section: Introductionmentioning
confidence: 99%
“…Haerens et al, 2013;Hagger et al, 2007;Tilga et al, 2017;Williams & Deci, 1996) and Spanish (e.g. Burgueño et al, 2020;Granero-Gallegos et al, 2014;Moreno-Murcia et al, 2008) settings. Only two studies used tools that also measured competence and relatedness supportive behaviors from PE teachers (see Sa´nchez-Oliva et al, 2013;Van den Berghe et al, 2015), even though these tools have been rarely used.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, fulfilling one's need for autonomy with regard to decisions and behaviors translates into an improved psychological well-being. In the educational field, nonetheless, autonomy is equally relevant for the learning process, given that the student's decisions come together with exercising various capabilities that teachers shall encourage [16]. The teacher's behavior in the classroom in terms of autonomy support is paramount in order to help achieve higher levels of motivation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration that students may interpret autonomy support from PE teachers in a differentiated way, it is not only enough to provide autonomy support for students, but it would also be essential to understand how students perceive autonomy support from their PE teacher (Aguado-Gómez et al, 2016). In Spain, although previous studies have widely shown promising results in explaining learning consequences related to PE in students, they have used unidimensional measures of the students' perception of autonomy support from PE teachers such as the Spanish version (Granero-Gallegos et al, 2014) of the Learning Climate Questionnaire (Williams & Deci, 1996) adapted to PE or the Perceived Autonomy Support Scale for Exercise Settings (Hagger et al, 2007) in its Spanish version also adapted to PE (Moreno-Murcia et al, 2008). Whether the content of its items is, respectively, analyzed, these instruments only capture the cognitive element of autonomy support from PE teachers, ignoring its procedural and organizational dimensions.…”
mentioning
confidence: 99%